Researching Educational Technology - Wegerif, Rupert; Major, Louis (The Theory of Educational Technology, 2023)
In this chapter, we explore the role of theory in educational technology research and ask what the role of theory should be. We begin with a brief history of education and educational technology research. This history suggests these fields have been dominated by ideas about research that are rooted in the affordances of print technology, in a way that does not fit the needs and affordances of digital technology. We also establish how there has been an unproductive alternation between what we call ‘inside’ views, how things feel to participants, and what we call ‘outside’ views, such as statistical patterns in data. It appears that new digital technology not only makes new ways of doing educational research possible, but it also changes how we should think about the purpose and nature of educational research. We end by proposing relatively new methodologies and paradigms influenced by dialogic theory that respond to these historical challenges and are better suited to researching educational technology.
Num Pages: 21